2014
DOI: 10.1002/bse.1840
|View full text |Cite
|
Sign up to set email alerts
|

Board Effectiveness and the Voluntary Disclosure of Climate Change Information

Abstract: This paper examines the relationship between board of directors' effectiveness and voluntary climate change disclosures. Since risk management and reporting fall under the board's responsibility, we relate board effectiveness to the firm's decision to voluntarily respond to the Carbon Disclosure Project (CDP) annual questionnaire as well as the quality of disclosures about climate-change-related risks and strategies to mitigate them.Our results show a positive association between board effectiveness and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
167
3
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(199 citation statements)
references
References 58 publications
(105 reference statements)
8
167
3
3
Order By: Relevance
“…In this framework, it is suggested that the board of directors is the ultimate internal control mechanism for overseeing managers (agents) on behalf of shareholders and other stakeholders (Rupley at al. 2012;Eng and Mak 2003;Said et al 2009;Ben-Amar and McIlkenny 2015). From this point of view, this study primarily aims to merge corporate governance literature and environmental disclosure literature by analyzing the relationship between corporate governance, in particular board characteristics, and the extent of environmental disclosures of Turkish companies.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In this framework, it is suggested that the board of directors is the ultimate internal control mechanism for overseeing managers (agents) on behalf of shareholders and other stakeholders (Rupley at al. 2012;Eng and Mak 2003;Said et al 2009;Ben-Amar and McIlkenny 2015). From this point of view, this study primarily aims to merge corporate governance literature and environmental disclosure literature by analyzing the relationship between corporate governance, in particular board characteristics, and the extent of environmental disclosures of Turkish companies.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Second, little is known about how this nexus changes in the presence of specific features of the TMT. Preceding studies have examined board and governance characteristics, as the main determinants of firm's social/environmental management and financial performance (Ben‐Amar & McIlkenny, ; Chang, Li, & Lu, ; Eleftheriadis & Anagnostopoulou, ; Galbreath, , ; Haque & Ntim, ; Jizi, ; Lau, Lu, & Liang, ; McGuinness, Vieito, & Wang, ; Ntim, ; Sullivan & Gouldson, ). Nevertheless, these scholars have neither investigated the impact of TMT characteristics on environmental performance/financial distress nor how they can moderate environmental performance–financial distress nexus.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Berthelot and Robert () show that the presence of an environmental committee is associated with a higher level of climate change disclosure to the Canadian Institute of Chartered Accountant by oil and gas firms. Moreover, Ben‐Amar and McIlkenny () show a positive association between board effectiveness—proxied by the Board Shareholder Confidence Index—a firm's decision to participate in the CDP, as well as its carbon disclosure level and transparency . Finally, Peters and Romi () find that the presence of an environment committee and a CSO is positively associated with the likelihood of carbon disclosure and that CSOs are associated with disclosure transparency.…”
Section: Theory and Hypothesesmentioning
confidence: 99%